A One Year Study of Newly Constructed Broiler Houses for the Prevalence of Campylobacter - Eberle, K.N.; Davis, J.D.; Purswell, J.P.; Parker, H.M.; McDaniel, C.D.; Kiess , A.S. (International Journal of Poultry Science, 2012)
In 2009, the USDA Food Safety and Inspection Service announced the development of new pathogen reduction performance standards for Salmonella and Campylobacter both on-farm and in the processing plant. The objective of this study was to evaluate the prevalence and distribution of Campylobacter in 3 newly constructed broiler houses for the first 4 flocks placed. Litter and fecal samples were collected from each house at 0, 28 and 48 d of production. Samples were serially diluted and spread onto Campy Cefex agar plates. Two 40 mL water samples were collected each production day and filtered through a 0.45 μm membrane before being placed onto a Campy Cefex agar plate. All plates were purged with a microaerophilic gas and incubated for 36 h at 42°C. Individual plates were screened for characteristic Campylobacter colonies and suspect colonies were confirmed using a latex agglutination kit. An additional 50 g of litter was collected from the evaporative cooling inlets, middle and tunnel ventilation fans to determine litter moisture and pH. Inside and outside temperatures were also collected. Out of 2300 litter, 900 fecal and 45 water samples, only 5, 6 and 1 of the collected samples, respectively, were confirmed Campylobacter positive. The middle of the house contained a higher litter moisture level (37%) than the evaporative cooling inlet end (33%) and tunnel ventilation fan end (34%) (p<0.05). Litter pH was not different across days, locations or flocks. Temperature averaged 26.8oC inside and 27.6oC outside. In conclusion, the newly constructed houses did not show a high prevalence of Campylobacter. Litter moisture was at levels conducive for Campylobacter growth. The high litter pH and low temperatures, along with other on-farm management strategies and the fact the broiler houses were brand new, may have suppressed Campylobacter’s ability to colonize the litter.